Species delimitation of the genus Champia (Rhodymeniales, Rhodophyta) from Korea using DNA barcoding - Young-Ho Koh; Ga-Youn Cho (Journal of Ecology and Environment)
DNA barcoding is becoming a widely applied tool to accurately discriminate red algae. We tested the effectiveness of DNA barcoding for identification and discovery of Champia species in Korea and clarified the phylogenetic relationships using the plastid rbcL gene. As results, we described four species of Champia such as C. inkyua sp. nov., C. recta Noda, C. bifida Okamura, and C. expansa Yendo. A new species, C. inkyua, is characterized by entangled thallus, terete and irregular branches, hooked apices, and longitudinal filaments running throughout the frond periphery only. Longitudinal filaments were composed of a complete cell with two half cells between diaphragms in the cavity. C. recta and C. bifida were reinstated with previously used names of C. parvula and C. compressa, respectively. C. recta is the first recorded species from Korea and is characterized by an erect thallus, terete and irregular branches, and straight apices. C. bifida is characterized by compressed thallus, pinnate or alternate branches, and bifid apices. C. expansa is characterized by flabellate thallus and dichotomous branches. Molecular analyses of COI and rbcL genes revealed sufficient sequence divergence to warrant species recognition in the genus Champia.